Konflik Turki-Israel : Kajian Pada Era Erdogan Sebagai Perdana Menteri (2003-2014): The Turkish-Israeli Conflict: A Study During Erdogan's Era as Prime Minister (2003-2014) - Nor Hidayah, Nur Syahirah; Mohd Nor, Mohd Roslan; Ibrahim, Muhammad Khalis (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
The Republic of Turkey is a country that practices a secular system. In 1945, Turkey, with a majority of its population being Muslims, recognized the existence of Israel and made agreements to cooperate in political, economic, and military aspects. However, after the AK Party, with Erdogan as Prime Minister, came to power, there were reforms in Turkey's foreign policy that resulted in changes in the cooperation between these two countries, leading to crises between Turkey and Israel. The main objective of this study is to discuss Erdogan's appointment as Prime Minister of Turkey, analyze the new foreign policy introduced by Erdogan, and explain the conflicts that occurred between Turkey and Israel during Erdogan's tenure as Prime Minister of Turkey. Additionally, this study employs three methods, namely data collection, data sources, and data analysis. Data collection and data sources are obtained from previous studies. This research will provide an understanding of the crises between Turkey and Israel due to changes in Turkey's foreign policy during Erdogan's time as Prime Minister of Turkey.